2019
DOI: 10.1021/jacs.9b07755
|View full text |Cite
|
Sign up to set email alerts
|

Light-Responsive, Shape-Switchable Block Copolymer Particles

Abstract: A robust strategy is developed for preparing light-responsive block copolymer (BCP) particles in which shape and color can be actively controlled with high spatial and temporal resolution. The key to achieving light-responsive shape transitions of BCP particles is the design and synthesis of surfactants containing light-active groups (i.e., nitrobenzyl esters and coumarin esters) that modulate the amphiphilicity and interfacial activity of the surfactants in response to light of a specific wavelength. These li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
94
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 65 publications
0
94
0
Order By: Relevance
“…Responsive morphological transformations of internally ordered colloidal polymer particles are of great interest due to their potential as smart nanomaterials for applications in sensors, detection, anti-fake, etc. [8,32,33] 3D confined thermal-or solvent-annealing enables morphological transformations of nanostructured colloidal polymer particles in a controllable manner. [34,35] Previously, we have demonstrated how interfacial interaction drives BCP segment orientation (e.g., from parallelto concentric-lamellar) within a 3D soft confined space upon solvent annealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responsive morphological transformations of internally ordered colloidal polymer particles are of great interest due to their potential as smart nanomaterials for applications in sensors, detection, anti-fake, etc. [8,32,33] 3D confined thermal-or solvent-annealing enables morphological transformations of nanostructured colloidal polymer particles in a controllable manner. [34,35] Previously, we have demonstrated how interfacial interaction drives BCP segment orientation (e.g., from parallelto concentric-lamellar) within a 3D soft confined space upon solvent annealing.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Recently, Kim et al extend this strategy by using a light responsive surfactant that can dynamically tune the interfacial interaction. [32] Besides, a switchable transformation between pupa-like and faveolated particles by changing the location of pH and/or temperature responsive additives were reported. [33,36] The addition or removal of additives can vary the volume fraction, thereby inducing the transformations in the internal structure of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, light has been considered as a flexible, precise, and non‐invasive element for “smart” therapy. [ 24–26 ] Majority of the light‐responsive materials is sensitive to ultraviolet, such as azobenzenes, [ 27 ] nitrobenzenes, [ 28 ] spiropyrans, [ 29 ] and diarylenes. [ 30 ] However, limitations of transformation and application still remain, because of the poor tissue penetration.…”
Section: Introductionmentioning
confidence: 99%
“…The external stimulus response provides a simple pathway for the controllable transformation of particle morphology on demand. [ 23,24 ] It has been reported that the use of pH, [ 10,25 ] temperature, [ 26,27 ] light, [ 28,29 ] and electric field [ 30–32 ] can cause changes in particles shape. For example, Weck et al.…”
Section: Introductionmentioning
confidence: 99%